PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KETERAMPILAN PROSES SAINS PADA PEMBELAJARAN IPAS DI SD - Aditya Putri, Nanda; Mustikaati, Wina; Permas Hikmatunisa , Nenden (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Science process skills are essential to develop and utilize in the science education process. This research was driven by deficiencies in processing abilities among elementary school students. The purpose of this study was to determine the impact of the inquiry learning model and the introduction of the guided inquiry learning model. This study employed an experimental approach, specifically a quasi-experimental design with a non-equivalent control group. The participants were fourth-grade students from SDN 1 Ciwareng. Data collection was carried out using pre-tests and post-tests. The findings indicated that the learning model had a significant effect, contributing 46.5% of the variance. Based on these results, the researchers recommend that future studies focus on science process skills from an informational perspective in other contexts.   Keywords: guided inquiry, learning model, science process skills